Pemanfaatan Sampah Organik Menjadi Ecoenzym Skala Rumah Tangga di Kelurahan Pangkalan Jati Cinere Depok - Noviana, Linda; Prinajati, Purnomosutji Dyah (Indonesia Berdaya, 2022)
Organic waste is waste that is easily biodegradable in the environment. However, if it is not managed properly, it will have an environmental impact and disrupt human health. One way to overcome the problem of organic waste is to make an ecoenzyme solution from organic waste. Ecoenzym is a natural solution that is versatile and can be used as a floor cleaner, cleaning household furniture and other uses. The location that will be used as an object for PKM is Pangkalanjati Baru village, Cinere Depok. This is because this area produces a lot of organic waste that has not been managed properly. The objectives of this PKM are: (1) Creating public awareness of managing waste. (2) Provide an understanding of the importance of waste management. (3) Provide knowledge on the manufacture of ecoenzymes from organic waste. (4) Provide skills in making ecoenzymes on a household scale. From the results obtained after participating in the training to make ecoenzymes, the knowledge of PKK women increased from 30% to 70%. Meanwhile, the skill in making ecoenzymes increased from 20% to 60%. In terms of skills, it was felt that they were not optimal due to the lack of available facilities and infrastructure and the women also had other duties in their PKK organization.